Reaching Out with Outlook Information - Sherrill Carlson (Journal of Applied Communications, 1986)
Reaching a large number of agricultural producers, the agricultural business/financial community and the public with agricultural outlook information sounds like one of those grandiose educational ideas that never have much reality beyond the pages of the annual plan of work.